Long-term management of contaminated sites - Leschine, Thomas M. (Research in social problems and public policy ;, 2007)
Even today, many people think of 'social problems' as involving poor and powerless individuals in society. "Research in Social Problems and Public Policy" seeks to improve the balance by adding a focus on important and powerful institutions. Such organizations often play key roles in managing, and mismanaging, the ways in which some of today's most important social problems are handled by the public policy system. The series presents papers that discuss policy sciences, public policy analysis and public management. This volume addresses operations and design issues for government organizations.